A series of thiophene- and nitrogen-rich conjugated microporous polymers for efficient iodine and carbon dioxide capture. (13th October 2021) - Wang, Li; Yao, Chan; Xie, Wei; Xu, Guangjuan; Zhang, Shuran; Xu, Yanhong
Abstract : A series of thiophene- and nitrogen-rich conjugated microporous polymers can be used for high iodine and carbon dioxide capture. Abstract : By selecting the building blocks with different active sites, 4-formylphenylboronic acid (FBA), 3, 3′, 5, 5′-tetrabromo-2, 2′-benzothiophene (DDT) and N, N ′, N ′′, N ′′′-tetra( p -phenylene) para -phenylenediamine (TABD), two conjugated microporous polymers (CMPs), SNCMP-1 and SNCMP-2, with multiple active sites were synthesized via a palladium(ii )-catalyzed coupling reaction. They exhibited excellent performances in volatile iodine capture with iodine adsorption values of 570 and 698 wt%, respectively. In addition, SNCMP-1 and SNCMP-2 displayed outstanding CO2 adsorption capacities with uptakes up to 3894 and 3878 mg g −1 at 70 bar and 323 K conditions, respectively.